Conventional Radiography and Ultrasound Imaging of Rheumatic Diseases Affecting the Pediatric Population - Pracoń, Grzegorz; Aparisi Gómez, Maria Pilar; Simoni, Paolo; Gietka, Piotr; Sudoł-Szopińska, Iwona (Seminars in Musculoskeletal Radiology, 2021)
Juvenile idiopathic arthritis is the most frequent rheumatic disease in the pediatric population, followed by systemic lupus erythematosus, juvenile scleroderma syndromes, juvenile dermatomyositis, chronic recurrent multifocal osteomyelitis, and juvenile vasculopathies. The imaging approach to inflammatory connective tissue diseases in childhood has not changed dramatically over the last decade, with radiographs still the leading method for bony pathology assessment, disease monitoring, and evaluation of growth disturbances. Ultrasonography is commonly used for early detection of alterations within the intra- and periarticular soft tissues, assessing their advancement and also disease monitoring. It offers several advantages in young patients including nonionizing radiation exposure, short examination time, and high resolution, allowing a detailed evaluation of the musculoskeletal system for the features of arthritis, tenosynovitis, enthesitis, bursitis, myositis, as well as pathologies of the skin, subdermis, vessels, and fasciae. In this pictorial essay we discuss radiographic and ultrasound inflammatory features of autoimmune pediatric inflammatory arthropathies: juvenile idiopathic arthritis, lupus erythematosus, juvenile scleroderma, juvenile dermatomyositis and polymyositis.
Keywords: juvenile idiopathic arthritis; systemic lupus erythematosus; juvenile scleroderma syndromes; juvenile dermatomyositis